Profile of women seeking fetal gender at ultrasound in a Nigerian obstetric population (2008)
Objective: To determine the proportion of women that wanted to know fetal gender at ultrasound, characterize them and document reasons for wanting to know fetal gender. Methodology: A cross-sectional study on consecutive pregnant women at 20 weeks or more gestation that presented for prenatal ultrasound at a private hospital in Nigeria from May to December 2005. Results: Of the 1135 women, 167 (14.7%) sought to know the fetal gender. Significant independent factors included ethnic group, as women from the predominant Hausa–Fulani were less likely when compared to those of other ethnic groups (OR: 0.4, 95% CI: 0.2–0.7). Women with tertiary education were 6.6 times (OR: 6.6, 95% CI: 3.3– 13.2) more likely. Women with a previous male baby were 30.6 times more likely (OR: 30.6, 95% CI: 13.6–68.5), while those with previous female baby were 54.3 times more likely (OR: 54.3; 95% CI: 23.4–125.8) to seek fetal gender. Main reasons for seeking fetal gender were preference for a particular fetal gender (57%); what wears to buy for the baby (24%) and curiosity (18%). Conclusion: About 15% of the study group requested to know fetal gender and it was associated with ethnic group, maternal educational level and gender of the previous baby. The most common reason for wanting to know fetal gender was the desire for a particular gender